#TITLE_ALTERNATIVE# - MARULI TUA TAMBUNAN (NIM 13101022), ROBERT
The demand of energy, limitation of fossil energy resource, and environmental negative effects of using fossil energy resource cause to be necessary to use renewable energy resources. Wind energy is one of many kind renewable energy resources. Wind energy can be extracted by using of wind turbine. The type of wind turbine in this final project is 3.5 meters of diameter two blades horizontal axis upwind wind turbine with tail. The design process depends on manufacturability aspect and wind turbine performance to extract wind power. The research method is combination of design, production, modification and experimental. Computer program calculation was used to predict flow condition through airfoil cross section and to predict optimum angle of attack that provides the highest lift to drag ratio. Flow simulation was also used to predict flow condition through the wind turbine rotor, value of rotor torque, loading condition of rotor, and to predict the maximum pitch angle at determined operation condition. Wind turbine performance testing was performed to get the power versus wind speed characteristic curve of wind turbine and to get cut in speed value.